David Busch's Canon EOS Rebel T1i/500D guide to digital SLR photography - Busch, David D.; Safari eBooks (Boston, Mass. : Course Technology, 2010)
"David Busch's Canon EOS Rebel T1i/500D Guide to Digital SLR Photography shows you how to make the most of your camera's robust feature set, including 15 megapixel resolution, blazing fast automatic focus, the real-time preview system Live View, and full HD movie-making capabilities, to take outstanding photos and videos. You'll learn how, when, and, most importantly, why to use all the cool features and functions of your camera to take eye-popping photographs. This book is chock full of handson tips for choosing lenses, flash units, and software products to use with your new camera. Beautiful, full-color images illustrate where the essential buttons and dials are, so you'll quickly learn how to use your Canon EOS Rebel T1i/500D, and use it well"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Canon digital cameras -- Handbooks, manuals, etc; Single-lens reflex cameras -- Handbooks, manuals, etc; Photography -- Digital techniques; Electronic books